Post-translational Modification Control of HBV Biological Processes - Yang, Fan (Frontiers in Microbiology, 2018)
Hepatitis B virus infection remains a global healthy issue that needs to be urgently solved. Novel strategies for anti-viral therapy are based on exploring effective diagnostic markers and therapeutic targets of diseases caused by HBV infection. It is well established that not only viral proteins themselves or key factors from the host control the biological processes of HBV including replication, transcription, packaging and secretion. Protein post-translational modifications (PTMs), such as phosphorylation, acetylation, methylation and ubiquitnation, are shown to their function in controlling proteins activity, regulating proteins stability, promoting proteins interaction and altering proteins subcellular localization leading to modulating crucial signaling pathway and affecting cellular processes. This review focuses on the functions and effects of diverse PTMs in regulating important processes in HBV life cycle. The potential roles of PTMs in pathogenesis of HBV associated liver diseases are also discussed.